Neuroimaging Studies of Acupuncture on Low Back Pain: A Systematic Review - Wen, Qiao; Ma, Peihong; Dong, Xiaohui; Sun, Ruirui; Lan, Lei; Yin, Tao; Qu, Yuzhu; Liu, Yalan; Xiao, Qingqing; Zeng, Fang (Frontiers in Neuroscience, 2021)
Objectives: To investigate the study design and main outcomes of acupuncture neuroimaging studies on low back pain (LBP). Methods: Neuroimaging Studies of Acupuncture on LBP were collected from three English databases such as PubMed and four Chinese databases such as China National Knowledge Infrastructure (CNKI) from inception to December 31, 2020. Study selection, data extraction and assessment of risk of bias were performed independently by two investigators. The quality of studies was appraised with the Cochrane's risk of bias tools. Information on basic information, methodology, and brain imaging data were extracted. Results: The literature search returned 310 potentially eligible studies, 19 articles met inclusion criteria. 78.9% of studies chose manual acupuncture as the intervention, 89.5% of studies evaluated functional changes elicited by acupuncture, and 68.4% of studies used resting-state fMRI as imaging condition. The most frequently reported acupuncture induced brain alterations of LBP patients were in the prefrontal cortex, insula, cerebellum, primary somatosensory cortex, and anterior cingulate cortex. There was a significant correlation between improved clinical outcomes and changes in the brain. Conclusions: The results suggested that improving abnormal structure and functional activities in the brain of the LBP patient is an important mechanism of acupuncture treating for LBP. The brain regions involved in acupuncture analgesia for LBP were mainly located in the pain matrix, default mode network (DMN), salience network (SN), and descending pain modulatory system (DPMS). However, it was difficult to draw a generalized conclusion due to the heterogeneity of study designs. Further well-designed multi-modal neuroimaging studies investigating the mechanism of acupuncture on LBP are warranted.